The effect of HIIT training on developing specific speed endurance and defensive movement performance for basketball players aged (15-17) years - Hussein, Dr. Ahmed Ashhab Abdul; Hussein, Dr. Ali Ashhab Abdul (Sulaimani Journal for Humanities, 2026)
Sports training has witnessed significant development in modern methods and exercises, especially recently. This necessitates that those interested keep pace with these advancements by adopting modern programs and techniques. Following modern methods in training sessions is of great importance and has a positive impact on raising the physical and skill levels of athletes. Among these methods are HIIT (High-Intensity Interval Training), which includes training sessions with periods of high-intensity, alternating exertion followed by short rest periods. This increases intensity while conserving effort and time in a controlled manner, adapting to high pressures during training. The athlete utilizes their specific speed endurance and defensive movement throughout the game, relying on the anaerobic system for energy production. High-Intensity Interval Training (HIIT) is considered one of the best and most suitable modern methods for training in harmony with energy systems to develop specific biomechanical capabilities and skill performance according to the athletes' abilities. HIIT training includes a variety of high-intensity exercises with little rest, such as jumping, hopping, sit-ups, pull-ups, weight training, aerobics, and gymnastics. These exercises are practiced... Through repetition and continuous sets, without interruption, the player aims to reach peak performance levels within a specific timeframe using a structured training method. This method includes exercises such as box jumps at varying heights, forward jumps with alternating legs, squats combined with jumps in the air, and movement in different directions with varying speed and direction. This approach develops speed endurance and defensive movement skills in young basketball players, engaging all joints and muscles throughout the body. The research problem was identified through the researcher's field experience and observation of training sessions. It was found that existing training sessions lacked modern, high-intensity methods followed by short rest periods for all body parts of young basketball players. These methods contribute to raising the level of physical fitness and skill. Therefore, the researcher decided to address this problem and propose solutions by answering the following question: Does HIIT training have an effect on raising the level of speed endurance and defensive movement skills of basketball players aged 15-17 years? This provides a significant incentive for players to maintain their performance and thus develop their physical fitness during training sessions, ultimately helping them perform defensive movements more effectively. This research aims to develop a set of HIIT (High-Intensity Interval Training) exercises to improve the speed endurance and defensive movement performance of basketball players aged 15-17 years, and to determine the effect of HIIT exercises on developing these skills. The research hypotheses are as follows: There is a positive effect of HIIT training on developing speed endurance and defensive movement performance of basketball players aged (15-17) years. The research areas included the human field, which is the youth players of Al-Hilla Basketball Club for the (2024-2025) season in the center of Babylon Governorate, the time field, the period from (22/11/2024) to (10/3/2025), and the spatial field, the Sports Talent Hall in the center of Babylon Governorate. The researcher used the experimental method with the method of two equivalent groups with pre-test and post-test. The statistical research population was defined as basketball players aged (15-17) years for Al-Hilla Sports Club for the 2024-2025 season, whose number is 16 players. The sample was chosen randomly by way of lottery, with 12 players, and they were divided equally into two experimental and control groups, each group of 6 players. The training prepared by the researcher was given to the members of the experimental group. Afterwards, HIIT training was implemented, with its application lasting for two months at a rate of (3) units per week, and the total number of units for the training program was (24). Chapter Four included the presentation and discussion of the results. The most important conclusions reached by the researcher were that HIIT training had a positive effect on developing the specific speed endurance and defensive movement performance of basketball players aged (15-17) years. The most important recommendations were to emphasize the attention of all coaches to modern training methods and techniques for players with high intensity, due to their clear importance in raising and developing the physical and technical aspects, as well as conducting other research and studies that take into account the modern training methods and programs used to develop the variables that were applied in our research on other samples.